2013
DOI: 10.1111/aor.12042
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Carbon Dioxide Insufflation for Cerebral and Cardiac Protection During Open Heart Surgery: A Systematic Review and Meta‐Analysis

Abstract: In spite of widespread application around the world, there has been controversy on the cerebral and cardiac protection efficacy of carbon dioxide insufflation (CDI) during open heart surgery. To make a comprehensive evaluation, we screened all relevant published randomized controlled trials to perform the first systematic review and meta-analysis for CDI during open heart surgery. We searched PubMed, EMBASE, the Cochrane Controlled Clinical Trial register, WANFAN, CQVIP, and CNKI database for published article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…CO 2 atmosphere has been debatable. 37 , 38 Nevertheless, we believe that notwithstanding shortages in our randomization assumptions, our study still offers important insights that are relevant to surgical practice.…”
Section: Discussionmentioning
confidence: 97%
“…CO 2 atmosphere has been debatable. 37 , 38 Nevertheless, we believe that notwithstanding shortages in our randomization assumptions, our study still offers important insights that are relevant to surgical practice.…”
Section: Discussionmentioning
confidence: 97%
“…In such cases, the carbon dioxide insufflation of the open mediastinum might be an alternative option. [6][7][8] This study also shows that a gradual increase in cardiac output coupled with delayed and staged ventilation at the end of the cardioplegic arrest added little to the efficacy of the de-airing procedure in the group with intact pleurae and expanded lungs. However, we believe that gradual perfusion and ventilation of the lungs adds safety to the de-airing method in which bilateral, induced pulmonary collapse is the key factor for effective de-airing.…”
Section: Discussionmentioning
confidence: 61%
“…In such cases, the carbon dioxide insufflation of the open mediastinum might be an alternative option. 68…”
Section: Discussionmentioning
confidence: 99%
“…However, the behavior of carbon dioxide in the actual operating field (ie, open thorax) has not been well studied. 2,3 In the present study, Vandenberghe and colleagues 1 successfully visualized the current of carbon dioxide using a Charged Coupled Device camera and the Schlieren technique. They demonstrated that carbon dioxide behaviors varied depending on the diffusor types, gas delivery flow rate, hand motions, and use of suction in the field.…”
Section: Hidefumi Nishida MD and Takeyoshi Ota Md Phdmentioning
confidence: 69%